2013
DOI: 10.3109/07434618.2013.849754
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Cognition on Young Children's Ability to Navigate a Speech-Generating Device

Abstract: This study examined the impact of cognition on young children's ability to navigate a speech-generating device (SGD) with dynamic paging. Knowledge of which cognitive factors impact navigational skills could help clinicians select the most appropriate SGD for children who have complex communication needs. A total of 65 typically developing children aged 48-77 months were assessed using the Leiter International Performance Scale-Revised (Leiter-R) and the Automated Working Memory Assessment (AWMA). Although sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…For both studies that used this methodology 1,2 , cognition was correlated to navigational scores. The higher the cognitive scores were, the higher were the navigational scores 1,2 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For both studies that used this methodology 1,2 , cognition was correlated to navigational scores. The higher the cognitive scores were, the higher were the navigational scores 1,2 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…The ability to navigate between these levels is required in order to find symbols within the multiple levels of an SGD 6,7 . The importance of cognitive skills in the ability to navigate the levels of an SGD has been demonstrated 1,2,4 . Results of a study that analyzed the impact of language abilities on navigational skills revealed that language skills were not a good predictor of navigational skills among children 8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations